DIMENSI MELAYU DALAM PUISI TERSEBAB AKU MELAYU: BUKU SAJAK PENGGAL KEDUA KARYA TAUFIK IKRAM JAMIL ‘KAJIAN STRUKTURALISME GENETIK’ - Marini Rehanisafira; Nurizzati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Poetry as a literary work contains the author's thoughts related to social reality in society. This allows poetry to be analyzed regarding the creation of its origins which reflect portraits of life using the study of genetic structuralism. One of the poems that can be studied using genetic structuralism is the poem Tersebab Aku Melayu: Buku Sajak Penggal Kedua by Taufik Ikram Jamil regarding the Malay dimension. This study aims to describe the relationship between the structure of poetry and social structure, human facts, and the author's worldview in the poem Tersebab Aku Melayu: Buku Sajak Penggal Kedua by Taufik Ikram Jamil with a study of genetic structuralism that describes the Malay dimension. The type of research used is qualitative research with content analysis methods. Data collection techniques to be carried out are reading techniques and note-taking techniques. The data analysis technique will be carried out using the following steps: (1) classifying and coding data related to the research problem; (2) interpreting data related to the study of genetic structuralism; (3) draw conclusions from the results of data analysis to see an explanation of genetic structuralism; (4) make a report in accordance with the research. The results of the study suggest that the relationship between the structure of poetry and social structure in the poem Tersebab Aku Melayu: Buku Sajak Penggal Kedua by Taufik Ikram Jamil can be seen from the diction on the physical structure and the themes on the inner structure which describe the Malay dimension regarding the social structure of Malay society which consists of several levels in the narrative of Malay history, the dominant human facts are social facts explaining behavior among Malay people, and the author's worldview is related to the social life of the Malay community which is based on the values ​​of Tunjuk Teachings of Malay and Islamic principles based on the Qur'an and Hadith.